Constraints on Higgs Effective Couplings in Hνν¯ Production of CLIC at 380 GeV - H. Denizli; A. Senol (Advances in High Energy Physics)
The potential of the e+e-→νν¯H process in the first stage of CLIC considering center-of-mass energy of 380 GeV and assuming the baseline integrated luminosity of 500 fb-1 is examined to probe CP-conserving dimension-six operators in a model-independent Standard Model effective field theory framework. In the analysis, a detailed fast simulation on e+e-→νν¯H signal processes and dominant backgrounds is performed including parton showering with PYTHIA and detector simulation based on ILD type detector with DELPHES in MadGraph. The obtained best limits on c¯HB, c¯W=-c¯B, and c¯HW are -4.82;1.53×10-2, -5.11;4.13×10-3, and -6.58;5.55×10-3, respectively.